2024
DOI: 10.1021/acs.analchem.3c04625
|View full text |Cite
|
Sign up to set email alerts
|

Dual Friction Force/Fluorescence Microscopy

Jianlu Zheng,
Bratati Das,
Kaori Sugihara

Abstract: Friction force microscopy (FFM) is a mode of atomic force microscopy (AFM) that quantifies both normal and horizontal forces against substrates. Recent improvement in its accuracy at nanonewton ranges and the possibility of combining AFM with fluorescence microscopy enabled the simultaneous characterization by FFM and fluorescence microscopy. This Tutorial describes the operation principle of the dual friction force/fluorescence microscopy setup and highlights its emerging applications in mechanochromic materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Gold-coated silicon nitride triangular probes with a spring constant of approximately k = 26 N/m (AC160TSA-R3, Oxford Instruments, UK) were used for all the measurements. The actual vertical spring constant, K v , was calibrated through the thermal noise method. , The deflection sensitivity was roughly estimated from the force curve on the substrate (control experiment). Nevertheless, each force curve on PDA films was further corrected in such a way that the curve on the solid substrate (region iii in Figure e) becomes vertical as glass is incompressive.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold-coated silicon nitride triangular probes with a spring constant of approximately k = 26 N/m (AC160TSA-R3, Oxford Instruments, UK) were used for all the measurements. The actual vertical spring constant, K v , was calibrated through the thermal noise method. , The deflection sensitivity was roughly estimated from the force curve on the substrate (control experiment). Nevertheless, each force curve on PDA films was further corrected in such a way that the curve on the solid substrate (region iii in Figure e) becomes vertical as glass is incompressive.…”
Section: Methodsmentioning
confidence: 99%
“…A limitation in their experiments was that the measured shear forces were qualitative, as the standard AFM quantifies only vertical forces. To overcome this issue, recently, we have introduced friction force microscopy, a mode of AFM that quantifies both vertical and lateral (shear) forces, , to provide quantitative evidence for the anisotropic mechanochromism. , Based on the same technique, we have also found that Young’s modulus of PDA films is strongly correlated with their force sensitivities at the nanoscale, where softer PDAs are more force sensitive . These local force applications by AFM tips are believed to induce a crystal-to-amorphous transition in the PDA structure by breaking the inter- and intramolecular interactions, such as hydrogen bonds between PDA headgroups and the hydrophobic interactions between the alkyl chains, as the morphology after AFM scanning was typically rougher.…”
Section: Introductionmentioning
confidence: 99%